Karakteristik Roti Manis Berbahan Dasar Pati Sagu HMT (Heat Moisture Treatment) Dengan Penambahan Konsentrasi Bubuk Cengkeh (Syzygium aromaticum) - Rumatumia, Hatija; Breemer, Rachel; Picauly, Priscillia (Jurnal Agrosilvopasture-Tech, 2023)
The objective of this research was to identify the optimal clove powder concentration for HMT sago starch sweet bread. This study employed a single factor completely randomized design (CRD) with four treatment levels, i.e., 0%, 0.3%, 0.5%, and 0.7% clove powder. Observed variables consist of moisture, ash, fat, and total sugar content. Observation variables for the hedonic quality test include color, aroma, texture, and appearance. The results showed that the addition of clove powder at a concentration of 0.7% was able to preserve the quality of sweet bread made from HMT sago starch for 6 days of storage with chemical characteristics of 27.60% moisture content, 2.35% ash content, 0.888% fat content, and 9.69% total sugar. The bread produced with HMT sago starch had a slightly brown color, a firm texture, a mildly aromatic flavor, and no moldy appearance.